Food prices and poverty reduction in the long run - Headey, Derek D. (International Food Policy Research Institute, 2014)
Standard microeconomic methods consistently suggest that, in the short run, higher food prices increase poverty in developing countries. In contrast, macroeconomic models that allow for an agricultural supply response and consequent wage adjustments suggest that the poor ultimately benefit from higher food prices. In this paper we use international data to systematically test the relationship between changes in domestic food prices and changes in poverty. We find robust evidence that in the long run (one to five years) higher food prices reduce poverty and inequality. The magnitudes of these effects vary across specifications and are not precisely estimated, but they are large enough to suggest that the recent increase in global food prices has significantly accelerated the rate of global poverty reduction.